Absence-to-bilateral-tonic-clonic seizure: A generalized seizure type. (6th October 2020) - Beniczky, Sándor; Rubboli, Guido; Covanis, Athanasios; Sperling, Michael R.
Abstract : Objective: To test the hypothesis that absence seizures can evolve to generalized tonic-clonic seizures, we documented electroclinical features of this novel seizure type. Methods: In 4 large video-EEG databases, we identified recordings of seizures starting with impaired awareness that, without returning to baseline interictal state, evolved to generalized tonic-clonic seizures. We extracted the detailed semiologic and electrographic characteristics of these seizures, and we documented the clinical background, diagnoses, and therapeutic responses in these patients. Results: We identified 12 seizures from 12 patients. All seizures started with a period of impaired awareness and bursts of generalized spike or polyspike and slow-wave discharges, the hallmark of absence seizures. Without returning to baseline, the nonmotor (absence) phase was followed by tonic-clonic convulsions. We called this novel generalized seizure type absence-to-bilateral-tonic-clonic seizure. Most patients had idiopathic generalized epilepsies, although with a high incidence of unusual features and poor therapeutic response. Conclusions: Absence-to-bilateral-tonic-clonic seizures are a novel generalized seizure type. Clinicians should be aware of this seizure for correctly diagnosing patients. This novel seizure type may further elucidate generalized ictogenesis.